The First Case Report of a Primary Mast Cell Tumor Originating from the Inguinal Lymph Node in a Nine-Year-Old Female Maltese Dog and a Comparative Literature Review in Humans - Nuri Lee; Gibum Kwon; Kyuhyung Choi (Life)
Here, the authors report the first case of a primary mast cell tumor originating from the inguinal lymph node in a nine-year-old intact female Maltese dog that had undergone a left ureteral stent, ureterotomy and splenectomy, and left-side mastectomy, including inguinal lymph node removal and ovariohysterectomy, in South Korea in May 2024. The splenic mass, mammary gland mass, and inguinal lymph node underwent histopathological examination, resulting in the diagnosis of nodular hyperplasia, grade 1 mammary complex carcinoma, and a mast cell tumor (MCT), respectively. To clarify the origin of the MCT from the inguinal lymph node, a computed tomography (CT) scan was performed. In addition, through a blood smear test, mast cell leukemia was ruled out. After CT scanning by veterinary radiologists and a biopsy of all possible masses, it was finally concluded that the MCT primarily originated from lymph nodes, which is extremely rare in dogs. The patient is recovering well as of February 2025, just 7 months after the first diagnosis, following surgery and 16 weeks of chemotherapy with a combination of prednisolone and vinblastine, considering the C-kit PCR results of the left inguinal lymph node after the surgical removal of the MCT. This report is significant for two reasons, firstly because of the rarity of MCTs originating from lymph nodes other than the skin and gastrointestinal organs, and secondly because the authors propose a hypothesis for the rarity of primary lymph node mast cell tumors and the correlation between mammary gland tumors and mast cell tumor growth based on a comparative literature review in humans, focusing on molecular mechanisms.